Impedance analysis of squirrel-cage induction motor at high harmonics condition - Aleksandr Skamyin; Yaroslav Shklyarskiy; Kirill Lobko; Vasiliy Dobush; Tole Sutikno; Mohd Hatta Jopri (Institute of Advanced Engineering and Science, 2024)
This study examines different methodologies for representing an asynchronous motor at higher harmonics by utilizing its equivalent circuit. Several approaches were compared based on simulation modeling. An experimental investigation was conducted in a laboratory setting using asynchronous electric motors with power ratings of 1.5 kW and 5.5 kW. The purpose of this investigation was to examine the characteristics of impedance in the presence of high-harmonic conditions. The generation of higher harmonics was achieved through the utilization of a precisely regulated thyristor rectifier in conjunction with a thyristor power controller. The findings indicate that the load on the shaft solely impacts the resistance at the fundamental harmonic, while the resistance at higher harmonics remains unaffected by the operating mode of the asynchronous motor (AM).